GrailKnights : an automaton mass manipulation package for enhanced pattern analysis - Du Preez, Hercule (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSC (Mathematical Sciences. Computer Science))--Stellenbosch University, 2008.